Expression of tumor necrosis factor-alpha receptor 2 and interleukin-1 in middle ear cholesteatoma - Vranješ Dalibor; Spremo Slobodan; Gajanin Radoslav; Špirić Sanja; Amidžić Ljiljana; Novaković-Bursać Snježana (Vojnosanitetski Pregled)
Background/Aim. Cholesteatoma is characterized by progressive growth with the erosion of surrounding bone due to pressure effects, enzymatic activity and activation of osteoclasts. The aim of this study was to examine the expression levels of tumor necrosis factor (TNF)-alpha receptor 2 (TNF R2) and interleukin-1 (IL-1) in chronic otitis media (COM) with and without acquired cholesteatoma and correlate them with the degree of bone destruction. Methods. The study included 178 patients of both sexes, aged 5–75 years, who underwent microsurgical treatment for COM, with and without cholesteatoma at the Ear, Nose and Throat Department, University Clinical Center of Republika Srpska (UCC RS), Banja Luka from 2015 to 2018. Based on cholesteatoma presence, the patients with COM were divided into two groups: with cholesteatoma (CCOM) (n = 97) and without cholesteatoma (COMWC) (n = 81). Samples of cholesteatoma perimatrix in the CCOM group and tympanic cavity inflamed mucosa in the COMWC group were collected intraoperatively. Intraoperative exploration of the middle ear included the status of the ossicular chain, individual ossicles, osseous walls of the external auditory canal (EAC) and tympanic cavity. Expression levels of TNF R2 and IL-1 were investigated by immunohistochemical analysis of tissue samples obtained during ear surgery. Results. The correlation between the level of osteodestruction and the presence of cholesteatoma was significant (p < 0.01). Elevated expression levels of TNF R2 and IL-1 were most frequent in CCOM patients with osteodestruction. The probability of osteodestruction of EAC and tympanic cavity walls was significantly higher in patients with high TNF R2 expression (p < 0.05). With respect to IL-1 expression levels, no significant correlation with the described pathomorphological changes was observed. Correlation between TNF R2 and IL-1 expressions and ossicular chain destruction was significant (p < 0.01). Conclusion. Cholesteatoma presence and elevated expression levels of TNF R2 and IL-1 in COM patients are significantly correlated. Expression levels of TNF R2 and IL-1 in acquired cholesteatoma tissue have a potential clinical significance for the occurrence of bone destruction compared to expression levels in inflamed mucosa of the tympanic cavity.